Characterization and Mapping of the Causes, Intensity and Effects of Natural Resource Use Conflicts in Kilosa and Mvomero, Tanzania - Mussa, Kassim R.; Mwamakimbullah, Reuben; Mahonge, Christopher P. (JNRD - Journal of Natural Resources and Development, 2019)
Tanzania has experienced many natural resource use conflicts in many parts of the country, including the Kilosa and Mvomero districts, ranging from family disputes through to all-out social unrest. Despite some efforts to curb rampant natural resource use conflicts, there is overwhelming evidence of the existence and upsurge of such conflicts, leading to various consequences, including death of people involved, destruction of property and the creation of a sense of insecurity. This study aims to characterize and map the causes, intensity and effects of natural resource use conflicts in the districts of Kilosa and Mvomero, Tanzania. Key Informant Interviews were used to gather valuable evidence to characterize the natural resource use conflicts in Kilosa and Mvomero, which also aided in constructing natural resource-use conflict typology. Quantum GIS software was used for spatial mapping of the conflicts. The study confirmed that land, water, crops, pasture and minerals are the main natural resources behind the conflicts, and therefore these resources have to be treated as crucial dimensions of conflict prevention in Kilosa and Mvomero. Generally, there is complexity in the conflict situations and overlapping of causes and conflict types on the one hand, and overlapping of conflict types and resources which are contested for on the other.